Pengaruh Abu Vulkanik Hasil Erupsi Merapi Dan Pupuk Kandang Terhadap Sifat Fisika Tanah Dan Hasil Kacang Tanah Pada Regosol Abu Vulkan Di Sleman, DIY - Adrinoviarini, Adrinoviarini; Supriyanto N., Supriyanto N.; Djadmo K., Bambang (Jurnal Magrobis, 2014)
The low content of colloid material such as clay and organic matter in sandy soil (volcanic ash Regosol) cause the soil less supportive in water and nutrient. Mount Merapi eruption in September 2010 is a natural process. The problem is the amount of ashfall which is different on each place. The legume is suggested to give a better effect on soil fertility due to enrichment of N content in the soil after the eruption.The experiment was conducted in a green house of Soil Departement, Agriculture Faculty of Gadjah Mada University from February to May 2011. The experiment was carried out using two blocks of two factorial arranged in completely random design. Each combination was replicated three times.The results showed that ashfall, chicken manure and cow manure increase slow drainage pore and N uptake. This treatment decrease total porosity, non usefull pores, water holding pores and quick drainage pores. Chicken manure and cow manure tend to generate rate of plant height at first to fifth week of growth. The rate of application of 30 tons/ha chicken manure and 10 tons/ha cow manure resulted in the highest growth compared to other treatments. The treatment of chicken manure tend to increase seed weight and 13.39 tons/ha cow manure tend to produce optimal seed weight. The optimum production of peanut is achieved by addition 10 tons/ha ashfall and 20 tons/ha cow manure. This mixture may be used as a recommendation to produce the optimal fertility condition for the volcanic ash Regosol.Key words: ashfall regosol, ashfall, chicken manure, cow manure, peanut.